Pillows, Cushions and Tuffets - Zentgraf, Carol (Lola Krause Publication, 2004)
Over 50 pillow, tuffet, and cushion projects Clear, easy, step-by-step directions and abundant photographs Great tips on fabric selection, assembly, and sewing techniques Much of the fun of decorating is mixing and matching fabrics to create an inviting ensemble, and you'll find plenty of ideas in Pillows, Cushions, Tuffets. Author Carol Zentgraf shows you how to choose the fabrics and embellishments to create dozens of pillows, cushions, and tuffets - from funky to upscale designs. Inside, you'll learn all the sewing techniques and trade secrets to create gorgeous accessories for every room in your home
Include Color Illustration
Keywords: Pillows -- Cushions -- Embroidery